Multi-photon tolerant protocols for quantum secure communication in wireless standards. (2016) - Nomula, Rupesh; Rifai, Mayssaa El; Verma, Pramode
This paper presents the integration of multi-photon tolerant quantum key distribution (QKD) protocols into three wireless communication standards. An analysis of the mode of operation and implementation of multi-photon tolerant QKD protocols in IEEE 802.11, WiMAX, and LTE wireless networks is presented along with the benefits and challenges of the proposed schemes. Traditional QKD based on the BB'84 protocol or its derivatives has relied on single photon protocols; however, the authors of this paper have opted to use multi-photon tolerant protocols. The choice of multi-photon tolerant protocols is based on the fact that not only the key distribution process is quantum-secure but also the other parameters (distance, data rate) of communication are maintained, which is not the case in single photon QKD approaches. This can be achieved since multi-photon tolerant protocols do not rely on the presence of no more than single photons per pulse to provide quantum-level security.